PSV-4 Peri-estrus ovarian, uterine, and hormonal variables influence the uterine luminal fluid metabolome in beef heifers. (8th October 2021) - da Silva, Felipe Alves Correa Carvalho; da Silva, Gabriela; Vieira, Bruna; Neto, Adomar; Rocha, Cecilia Constantino; Junior, Gilmar Arantes; Silva, Amanda; Lo Turco, Edson; Nogueira, Guilherme D; Pugliesi, Guilherme; Binelli, Mario
Abstract: In cattle, uterine luminal fluid (ULF) is the main source of molecules that support embryo development and survival during the peri-implantation period. Overarching hypothesis was that peri-estrus changes in ULF volume through accumulation and resorption mechanisms influence ULF composition during the estrous cycle and early pregnancy. Objectives were (1) to characterize individual temporal and spatial changes in ULF volume, endometrial and luteal vascularity, endometrial and luteal size, and progesterone (P4) concentrations during the peri-estrus period in beef heifers and, (2) associate such changes with the metabolite composition in the ULF, four days after estrus. Fourteen Bos indicus heifers that presented a PGF2α responsive CL received 500 µg PGF2α analog i.m. and were examined daily by rectal B-mode and pulse-wave color-Doppler ultrasonography until the fifth day after estrus (estrus = d 0). Plasma P4 was measured daily. On d 4, the uterine body was sampled using a cytology brush for targeted metabolomic analysis by mass spectrometry. Multivariate analyses clustered heifers according to ovarian, uterine, and hormonal variables in clusters A (n = 5) and B (n = 8 heifers). Individual metabolite concentrations were compared between clusters A and B by univariate analysis using t-test after FDR correction. Concentrations of Pro, Ala, Leu, Gly, Val, Lys, Ile, Phe, Asp, Orn, Tyr, Arg, Trp, Suc, Cit, ADMA, the sum of essential Amino Acids (AA), sum of non-essential AA, sum of aromatic AA, and total AA were greater in cluster A (FDR ≤ 0.05). ULF volume dynamics and associated uterine, ovarian, and hormonal variables during the peri-estrus period presented a concerted variation among heifers, which was associated with the ULF composition four days after estrus. Potential implications for embryo receptivity and reproductive outcomes are the focus of the current investigation.